Cross Reactive Cellular Immune Response to HCV Genotype 1 and 4 Antigens among Genotype 4 Exposed Subjects - Galal, Iman F. (Public Library of Science, 2014)
BACKGROUND: Hepatitis C Virus (HCV) infection is a global health burden particularly in Egypt, where HCV genotype 4a (GT-4a) predominates. The prevention and control of HCV infection will remain a challenge until the development of an effective vaccine that protects against different genotypes. Several HCV GT-1-based vaccines are in different stages of clinical trials, but antigenic differences could make protection against other genotypes problematic. In this regard, data comparing the cell-mediated immune (CMI) response to different HCV genotypes are limited. We aimed to ex vivo investigate whether GT-1-based vaccine may protect against HCV GT-4 infections. This was carried out on samples collected from genotype 4 infected/exposed subjects. METHODS/PRINCIPAL FINDINGS: The CMI responses of 35 subjects; infected with HCV GT-4/or who had spontaneously-resolved the infection and 10 healthy control subjects; to two sets of seven HCV overlapping 15-mer peptide pools derived from both genotypes; and covering most of the viral proteins; were evaluated. This was carried out using an interferon gamma (IFNγ) enzyme-linked immunospot (ELISpot) assay. Peripheral blood mononuclear cells (PBMC) from 17 subjects (48%) responded to at least one peptide pool derived from GT-1b/GT-4a with 13 subjects responding to peptide pools from both genotypes. A strong correlation was found in the responses to both genotypes (r = 0.82, p<0.001; 95% confidence interval = 0.562–0.933). The average IFNγ total spot forming cells (SFC)/10(6) PBMC (±SE) from the responding subjects for GT-1b and GT-4a was 216±56 and 199±55, respectively (p = 0.833). Also, there were no significant differences between those who cleared their HCV infection or who remained HCV-RNA positive (p = 0.8). CONCLUSION/SIGNIFICANCE: Our data suggest that an effective GT-1b vaccine could protect from GT-4a infection. These data could help in HCV rationale vaccine design and efficacy studies and further our understanding of HCV cross protection against different genotypes.